Comparison of functional outcomes and quality of life between transoral surgery and definitive chemoradiotherapy for oropharyngeal cancer. Issue 3 (3rd April 2014) - Chen, Allen M.; Daly, Megan E.; Luu, Quang; Donald, Paul J.; Farwell, D. Gregory
Abstract Background The purpose of this study was to compare patient‐reported outcomes between patients treated by initial transoral resection versus definitive chemoradiotherapy for oropharyngeal cancer. Methods Thirty‐one patients with oropharyngeal cancer treated by initial transoral CO2 laser microsurgery (n = 16) or robotic surgery (n = 15) followed by postoperative radiotherapy were identified. Each patient was matched to 1 control patient treated by definitive chemoradiotherapy. The University of Washington Quality of Life (UW‐QOL) scores at 1 year were compared. Results No significant differences were observed in any of the UW‐QOL functional domains at 1 year with the exception of swallowing (91.5 vs 72.1; p = .01). Twenty‐three of 31 patients (74%) treated by transoral surgery reported swallowing "as well as ever, " versus 10 of 31 patients (32%) treated by chemoradiotherapy. Conclusion Similar quality of life was observed among patients treated by transoral surgery or chemoradiotherapy. Although the rates of subjective swallowing dysfunction were higher among the latter, confounding biases must be considered. © 2014 Wiley Periodicals, Inc. Head Neck 37: 381–385, 2015